A light-mediated metal-free atom transfer radical chain transfer reaction for the controlled hydrogenation of poly(vinylidene fluoride-chlorotrifluoroethylene). Issue 2 (13th December 2017) - Tan, S. B.; Zhao, Y. F.; Zhang, W. W.; Gao, P.; Zhu, W. W.; Zhang, Z. C.
Abstract : A light-mediated atom transfer radical chain transfer process is proposed for the controlled hydrogenation of P(VDF-CTFE) using metal-free photocatalyst. Abstract : A light-mediated metal-free atom transfer radical chain transfer reaction (ATRCT) strategy is proposed for the controlled hydrogenation of poly(vinylidene fluoride-chlorotrifluoroethylene) (P(VDF-CTFE)) in present work. In this process, C–Cl bonds on CTFE units in P(VDF-CTFE) are firstly activated by the photoexcited catalyst under light. The subsequent chain transfer reaction of the generated macro-radicals to either polar solvents or chain transfer reagents could finely convert part or all the CTFE units into trifluoroethylenes (TrFEs) depending on the loading concentration of the chain transfer reagents and the reaction time. The hydrogenation reaction could be conducted under mild conditions and shows excellent controllable characteristics, which offers a facile, efficient, economic, and metal-free approach to synthesize P(VDF-TrFE) or P(VDF-TrFE-CTFE) from P(VDF-CTFE). In particular, this process could completely avoid issues associated with the residue of the metal ions in the target product, which have been recognized as the major resource of dielectric loss in the polymers utilized under high electric field.